Allocation of quality control stations in multistage manufacturing systems - Shetwan, Ali G.; Vitanov, Valentin; Tjahjono, Benny (Elsevier Science B.V., Amsterdam., 2011)
The allocation of quality control stations (AQCS) in multistage manufacturing systems has been studied extensively over the decades. This paper reviews the existing approaches, models comparison and solution techniques applied in AQCS. The relevance of the models and the effectiveness of the inspection strategies are examined by developing a generalised model. The conducting simulation experiments show that as the number of workstation increases the processing tine to solve the problem increases significantly. This led to the development of a heuristic algorithm with local search. The performance the heuristic was compared with the optimization method based on complete enumeration method (CEM). It was found that the heuristic method can derive an acceptable solution significantly faster than the CEM. The review has shown that the most common techniques used are dynamic programming and non-linear programming. The paper suggests some biologically inspired optimisation algorithms can be of interest for further study. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Manufacturing Quality Allocation Inspection optimisation serial production systems imperfect inspection operations off-line inspection economic optimization genetic algorithm optimal location configuration simulation model flow